2015
DOI: 10.1149/2.0231507jes
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Electroreduction on Platinum Nanoparticles Deposited onto D-Glucose Derived Carbon

Abstract: Microporous-mesoporous carbon material synthesized from D-(+)-glucose using hydrothermal carbonization method was used as a porous support for platinum nanoparticles catalyst for oxygen electroreduction reaction (ORR). The platinum nanoparticles were deposited onto the support using sodium borohydride reduction method. The XRD, HRTEM, HRSEM, EDX, Raman spectroscopy and low-temperature N 2 adsorption/desorption techniques were used to characterize the structures of unmodified and Pt-nanoclusters modified materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 40 publications
4
36
1
Order By: Relevance
“…While untreated hydrochars are reported to have very low surface areas below 100 m 2 g À1 , [16] which is consistent with the char from this study, activations of hydrochar are reported to increase specific surface areas. [26,[30][31][32] Here, the different activations led to an increase by a factor of 6 for physical and chemical activation and a factor of 7 for thermal activation. In other studies, areas after activation using KOH are, e.g., 2125 m 2 g À1 [24] and after activation using pyrolysis, e.g., 1190, [26] or 189 m 2 g À1 , [25] which strongly depends on processing parameters during activation and especially on the raw material for HTC.…”
Section: Activation Of Hydrocharmentioning
confidence: 99%
See 4 more Smart Citations
“…While untreated hydrochars are reported to have very low surface areas below 100 m 2 g À1 , [16] which is consistent with the char from this study, activations of hydrochar are reported to increase specific surface areas. [26,[30][31][32] Here, the different activations led to an increase by a factor of 6 for physical and chemical activation and a factor of 7 for thermal activation. In other studies, areas after activation using KOH are, e.g., 2125 m 2 g À1 [24] and after activation using pyrolysis, e.g., 1190, [26] or 189 m 2 g À1 , [25] which strongly depends on processing parameters during activation and especially on the raw material for HTC.…”
Section: Activation Of Hydrocharmentioning
confidence: 99%
“…[26,[30][31][32] Here, the different activations led to an increase by a factor of 6 for physical and chemical activation and a factor of 7 for thermal activation. In other studies, areas after activation using KOH are, e.g., 2125 m 2 g À1 [24] and after activation using pyrolysis, e.g., 1190, [26] or 189 m 2 g À1 , [25] which strongly depends on processing parameters during activation and especially on the raw material for HTC. Overall, BET analysis shows first that the porosity of each activated carbon from HTC is comparable to carbon black in terms of forming type II isotherms according to IUPAC classification and second that the specific surface areas of activated chars are much higher than the area of common carbon black.…”
Section: Activation Of Hydrocharmentioning
confidence: 99%
See 3 more Smart Citations